Threefold exTTF-based Buckycatcher - Radhakrishnan, Shankara Gayathri; Guldi, Dirk Michael; Perez, Emilio M.; Perez, Iria; Bietti, Massimo; Martin, Nazario (Journal of Coordination Chemistry, 2010)
Charge-transfer complex formation by a tuning-fork shaped π-extended tetrathiafulvalene-based molecule, which acts as molecular catcher for C in a variety of solvents upon photoexcitation, has been explored. An increase in 2-[9-(1, 3-dithiol-2-ylidene)anthracen-10(9H)-ylidene]-1, 3-dithiole unit creates an easy-chair like conformation accommodating C60, which leads to a binding constant and lifetime of radical ion pair state of 2.23 × 10 (mol L ) and 4.8 ps in ortho-dichlorobenzene. © 2010 Taylor & Francis.